Spontaneous Pneumomediastinum, Pneumothoraces and Surgical Emphysema in a COVID-19 Patient - Tshering, Dr Sonam; Siddiqui, Dr Saquib Navid; Ahmed, Dr Osman; Phuntsho, Dr Sangay (International Journal of Innovative Research in Medical Science, 2021)
Pneumomediastinum is defined as the presence of air or other gas in the mediastinum and is also known as mediastinal emphysema [1]. Pneumomediastinum can be categorized as spontaneous (SPM) or traumatic. Traumatic pneumomediastinum is caused by blunt or penetrating trauma to the chest, or iatrogenic injury, such as that produced by thoracic surgery. Mechanical ventilation is a common cause of barotrauma and pneumomediastinum. Pneumomediastinum caused by mechanical ventilation is often considered a type of traumatic pneumomediastinum, rather than SPM (UpToDate). We report a case of spontaneous pneumomediastinum, pneumothorax and surgical emphysema in a 20-year-old patient with COVID-19. He was managed conservatively.